An additively manufactured Al-14.1Mg-0.47Si-0.31Sc-0.17Zr alloy with high specific strength, good thermal stability and excellent corrosion resistance. (20th March 2021) - Bi, Jiang; Lei, Zhenglong; Chen, Yanbin; Chen, Xi; Lu, Nannan; Tian, Ze; Qin, Xikun
Abstract: A novel Al-14.1Mg-0.47Si-0.31Sc-0.17 Zr alloy was applied in the printing process of selective laser melting (SLM), and the corresponding microstructural feature, phase identification, tensile properties and corrosion behavior of the AlMgSiScZr alloy were studied in detail. As fabricated at 160 W and 200 mm/s, the Mg content of bulk sample decreased to 11.7 wt% due to the element vaporization at high energy density, and the density of this additively manufactured AlMgSiScZr alloy was 2.538 g/cm 3, which is 4.2 %∼8.5 % lighter than that of other SLM-processed Al alloys. After heat-treated (HT) at 325 ℃ and 6 h, the microstructure was almost unchanged with an alternate distribution of fine equiaxed crystals and coarse columnar crystals. Nano-sized Al3 (Sc, Zr) and Mg2 Si phases precipitated dispersedly in the Al matrix, and the tensile strength increased from 487.6 MPa to 578.4 MPa for precipitation strengthening and fine grain strengthening. With a fine grain size of 2.53 μm, an excellent corrosion resistance was obtained for the as-printed (AP) AlMgSiScZr alloy. While the corrosion resistance of HT sample decreased slightly for the formation of non-dense oxide layer and pitting corrosion induced by diffuse precipitation distribution. This SLM-printed AlMgSiScZr alloy with high specific strength, good thermal stability and excellent corrosion resistance has broad prospects for the aerospace and automotive applications.